KAJIAN KUALITAS AIR PERAIRAN SELAT MALAKA DESA KWALA INDAH DALAM UPAYA PENGENDALIAN PENCEMARAN AIR - Ria Retno; Mila Sianipar (Journal of Research and Publication Innovation, 2025)
One of the worst areas of marine environmental pollution is the Strait of Malacca because this Strait is busy with ships, especially giant tankers. The ecology of the Strait of Malacca is currently threatened with very severe pollution. The purpose of this study was to identify the air quality conditions in Kwala Indah Village, Sei Suka District, Malacca Strait Waters. The method used in this study is the purposive sampling method using the calculation of water pollution index at 3 sampling locations. Determination of water quality status using the pollution index method according to the Decree of the Minister of Environment 115/2003. The parameters observed and measured are 12 parameters using the Indonesian National Standard (SNI) method for measuring water and waste quality, including physical properties (temperature, brightness, current speed, salinity) and chemical properties (pH, dissolved oxygen, Biological oxygen demand, Nitrate, Nitrite, Ammonia, Orthophosphate and Silica. The pollution index in the waters of the Malacca Strait in Kwala Indah Village is included in the lightly polluted category with an average temperature of 28.78-29 °C, pH 7.57-8.16, BOD 14.38-14.45 mg/l and DO 2.2-2.6 mg/l. The strategy for controlling pollution in the Malacca Strait can be carried out by reducing the pollution load, namely by involving the community in environmental management.